Experimental investigation on swirling spray forced ignition of embedded multi-channel plasma igniter. (February 2021) - Cai, Banghuang; Song, Huimin; Wu, Yun; Jia, Min; Zhang, Zhibo
Abstract: An embedded multi-channel plasma igniter with C-shape and circular cavities is designed to solve the problem of secondary ignition and starting under extreme conditions, and compared with the surface multi-channel plasma igniter without cavity, the ignition process of three igniters at ground state and 12 km altitude state is recorded by high-speed camera. The results show that the ignition probability of C-shape embedded multi-channel plasma igniter is highest with the same fuel-air ratio, the ignition probability of reaching 100% is lower, and the advantage is more obvious at 12 km altitude state than at ground state. In the process of flame development, C-shape embedded multi-channel plasma igniter has the largest flame projection area, the fastest flame development speed and the shortest flame evolution time. At an altitude of 12 km, the flame stagnation stage occurs in the flame development process of the three igniters, and the ignition process of the embedded plasma igniter is less affected by the interference of air flow, which is more advantageous than the surface multi-channel plasma igniter. Flame instability occurs when the global fuel-air ratio approaches the lean ignition limit, and the flame stationary position is related to the flow field and the distribution of fuel-air ratio. The lean ignition fuel-air ratio increases exponentially as the height increases, and the advantages of C-shape embedded multi-channel plasma igniter become more and more obvious. Compared with the surface multi-channel plasma igniter, the widening percentage of lean ignition boundary of the C-shape embedded multi-channel plasma igniter can reach 21.4% at 12 km state, which is better than that of the circular embedded multi-channel plasma igniter. Highlights: An embedded multi-channel plasma igniter with C-shape and circular cavities was designed. The swirling spray forced ignition process of multi-channel plasma igniter was studied. The embedded multi-channel plasma igniter is more effective and advantageous.